Problems of the professional self-determination of modern senior pupils - Danylenko, G.N.; Shvets, A.N. (Environment & Health, 2017)
Objective: In the article we disclosed a concept and a content of the professional self-determination in the teenagers. The results of the study of the formation of professional self-determination in the senior pupils are presented in it. As a result of the study performed among the 9th grade pupils of the secondary schools of Ukraine aged 14-15 years, we determined that under equal conditions of the planning of the professional activity the further phased self-determination of the future specialty was stipulated not only by the psychological readiness for conscious choice but also by the state of health and the level of psychophysiological adaptation. Materials and methods: 982 pupils of secondary schools of Ukraine aged 14-15 years (493 boys and 489 girls) took part in the study. To study the level of the formation of professional readiness, we performed a survey with the help of the questionnaire, developed by the SI “Institute for Protection of Children’s and Teenagers’ Health, NAMS” which contained both alternative and ranked questions about the educational activity, planned education determination of the professional future, and professional awareness. Statistical processing of study materials was carried out with the help of MS Excel and SPSS-17. Results: The results of the study showed that professional intentions of the 9-graders are a key feature for the solution of the problem of higher school choice and future vocational activity. These intentions are contradictory in the most students due to the objective reason, such as a lack of school opportunity in the organization of the vocational guidance. The achieved level of the professional self-determination of the 9-graders differs depending on gender. The girls demonstrated higher indices of their professional self-determination. Age differences of the 9-graders don’t affect the process of the professional self-determination. The parents, Internet, teachers and school psychologists, classmates and friends are the main sources of the information about professional future. Radio, television, books, medical staff of the educational institution don’t affect significantly the choice of the profession and the level of professional self-determination in the 9-graders. Performed survey is sufficient for the analysis of the vocational guidance of the students. The professional choice of the students is formed under the effect of many factors which adjust both desire and aspiration. Therefore the studies on the vocational guidance require an integrated approach.